The relationship between psychological distress and cognitive failure among breast cancer survivors: a network analysis - Han, Bingxue; Yan, Jialin; Xiong, Ruoyu; Wang, Miaomiao; Liu, Jinxia; Jia, Liping; Dou, Jinhua; Liu, Xiaoli; Fan, Huaju; Li, Jianying; Zhang, Caiyun; Sun, Xiuhong; et al. (Frontiers in Psychology, 2024)
Background Psychological distress is highly prevalent and has a severe impact on the quality of life among breast cancer survivors. This type of distress is associated with cognitive failure. However, previous studies have focused solely on the total scale scores of these two concepts while ignoring the unique relationship between specific components. In the present study, we utilized network analysis to explore the relationship between psychological distress and cognitive failure in breast cancer survivors. Methods The network analysis approach was adopted to estimate the regularized partial correlation network in a cross-sectional sample of 409 breast cancer survivors. All participants were assessed using the Depression Anxiety Stress Scale and the Cognitive Failure Questionnaire. The Gaussian Graphical Model was employed to estimate the network, centrality indices, and edge weights, providing a description of the characteristics of the network. Results The results indicated that anxiety–stress and depression–stress were the strongest edges in the community of psychological distress. Distractibility–memory was the strongest edge in the community of cognitive failure. Distractibility and memory were the most central nodes, with the highest expected influence in the network. Depression and motor coordination acted as important bridge nodes with the highest bridge expected influence. Conclusion Distractibility and memory in cognitive failure played important roles in activating and maintaining the relationship network. Motor coordination was identified as the crucial pathway for the impact of cognitive failure on psychological distress. Interventions targeting these specific issues might be more effective in improving cognitive failure and reducing psychological distress among breast cancer survivors.